Hypoglycemic, Insulinotrophic and Cytotoxic Activity of three species of Ganoderma - Saufi Bastami, Mohd; Mohd Bohari, Siti Pauliena; M.H, Wong; Noor Wahab, Mohd; Rahmani, Ariffi Suraya; Rajab, Nor Fadilah; Hamid, Muhajir (Malaysian Journal of Science, 2007)
The crude extracts of Ganoderma lucidum, Ganoderma tropicum and Ganoderma tsugae were studied for insulinotrophic and hypoglycemic activities using rat pancreatic β-cell lines, BRIN-BD11 cells and normal Wistar rats. In an oral glucose tolerance test (OGTT), oral administration of 1 g/kg body weight of the crude extract resulted in a significant reduction in blood glucose in the normal rats. In acute 30 min insulin secretion tests, 1 mg/ml crude extract of all tested Ganoderma evoked a 1 - 4 fold stimulation of insulin secretion from the pancreatic β-cell lines. Of these, G. lucidum showed the highest insulinotrophic activity. In addition, cytotoxicity assay of extracts from G. lucidum, G. tropicum and G. tsugae towards rat pancreatic β-celliines showed half maximal inhibition (IC₅₀) at 200, 100 and 150µg/ml, respectively. These results demonstrated the presence of insulin-releasing and hypoglycemic activity in the crude extracts of G. lucidum, G. tropicum and G. tsugae.